HEMATOLOGICAL AND BIOCHEMICAL PREDICTORS OF COMPLICATIONS AND OUTCOMES AMONG PATIENTS WITH LYMPHOMA TREATED IN THE PALESTINIAN HEALTHCARE SYSTEM - Sbaihat, Baraa (An-Najah National University, 2024)
Background: Lymphomas are heterogeneous malignant neoplasm that form from unprogrammed proliferation of lymphocytes. Tumors arise in B cells, T cells, and N killer cells during their maturation stages. Lymphoma is divided into two main type , Hodgkin and non-Hodgkin lymphoma, and about 90 subtypes. There are multiple risk factors for lymphoma, including infection, immunodeficiency, autoimmune diseases, genetics, obesity, drugs, and environmental factors. Lymphoma is diagnosed beginning with a clinical examination, then using a CT scan and a biopsy to confirm the definitive diagnosis. The treatment plan for lymphoma patients is developed based on the stage of the disease and includes chemotherapy and radiation therapy. During the treatment period, the patient's status is monitored through periodic clinical examinations and laboratory tests. In Palestine, treatment is provided to lymphoma patients and their periodic examinations, disease progress, and treatment plan are followed up. Furthermore, the primary objective of this research is to examine the There is a relationship between biochemical and hematological factors and tests with complications ,outcomes and disease progression among lymphoma patients receiving treatment in Palestinian hospitals. Methods: In our study, we collected data for lymphoma patients includes age, date of diagnosis, gender, type of lymphoma, CBC tests, liver function tests, electrolytes, kidney function tests, and treatment receiving treatment in Palestinian hospitals at different ages and geographical regions for both males and females. The data for the patients was divided into two stages: the first stage, which is the stage of diagnosing the disease, and the second stage, which is the last examinations performed on the patients during their treatment path. Then tabulate the data in the Data Collection Form to be analyzed and obtain the research outputs. Results: This study was conducted on 150 lymphoma patients with median age of the patients 40.0 (29.0, 59.3) years and the mean age was 43.9 ± 18.2 years. of those 79 (52.7%) were male in gender ,118 (78.7%) had Hodgkin lymphoma. Time of diagnosis with median 5.0 (4.0, 7.0) years and the median time was 5.5 ± 2.6 years. The cancer stage was only available for a limited number of patients, 26 patients only, 17 (65.4%, 11.3% of all patients) were in stage II. The majority of patients reported general weakness 107 (71.3%),13 (8.7%) had cough, 27 (18.0%) had neck pain, 23 (15.3%) had dizziness, and 15 (10.0%) had fever. the comorbidities Accompaniment cancer were hypertension 14 (9.3%) , 14 (9.3%) diabetes mellitus, and 2 (1.3%) hypothyroidism. As part of the chemotherapy treatment(92.0%) of the patients were receiving cyclophosphamide, 61 (40.7%) received ondansetron and 90 (60.0%) received dexamethasone. In stage 1 Hodgkin lymphoma patients are of a younger age group and have lower survival rates higher white blood cell count, chloride , neutrophil granules, and platelets than non-Hodgkin lymphoma patients .On the other hand, in stage 2, there were no significant changes except for an increase in ferritin level in non-Hodgkin patients more than in Hodgkin patients. conclusion: In this study on a sample of Palestinian lymphoma patients, we found many relationships between lymphoma disease and its progression and risk factors that can increase the rate of lymphoma infection. These variables can contribute to future treatment plans or faster and better detection of cancer to limit its spread and confront it.
تنبؤات الدم والعوامل البيوكيميائية بالمضاعفات والنتائج لدى مرضى سرطان الغدد الليمفاوية الذين يتلقون العلاج في نظام الرعاية الصحي الفلسطيني